Estimation of the aerobic-anaerobic transition by heart rate variability in athletes and non-athletes subjects - Lopez-Fuenzalida, A.; Laroze N. D.; Berral de la Rosa, F. J.; Cancino L. J. (International Journal of Kinesiology & Sports Science, 2016)
Background: The estimate of aerobic-anaerobic threshold is commonly used for exercise prescription in athletes and non-athletes subjects; however, the methods currently used are expensive, and some of them use invasive techniques. The analysis of changes in heart rate variability during exercise may contribute to the introduction of a novel methodology to estimate the aerobic-anaerobic metabolic transition. Objective: The purpose of this study was to estimate the heart rate variability threshold (HRVT) through the Discrete Wavelet Transform (DWT) and compare the exercise intensities at which this happens to the moment when the aerobic-anaerobic metabolic transition occurs, estimated by the ventilatory threshold 2 (VT2) in athletes and non-athletes. Methods: 24 male subjects were enrolled (12 athletes; 12 non-athletes). Ventilatory parameters and R-R intervals were recorded breath by breath in a maximal incremental intensity exercise. HRVT was estimated through DWT and the VT2 was determined by 5 indicators: respiratory quotient =1.0, non-linear increase of the VE and VCO2, decrease of the PETCO2 and increase of the PETO2. Reserve heart rate frequency percentages (%RHRF) are determined, compared and correlated to VT2 (%RHRF-VT2) and HRVT (%RHRF-HRVT). We used a significance level of p<0.05 for all our analysis. Results: The results showed that there is no significant difference between the %RHRF-VT and %RHRF-HRVT in the assessed subject groups (total, athletes, non-athletes). There is a correlation between %RHRF-VT and %RHRF-HRVT in the whole group (r=0.91; p<0.001), athletes (r=0.84; p<0,001) and non-athletes (r=0.88; p<0,001). Conclusion: We conclude that the aerobic-anaerobic metabolic transition (i.e. VT2) during an incremental maximal exercise can be estimated through the HRVT measured by the DWT in athletes and non-athletes.